PENINGKATAN PENGETAHUAN DAN KETERAMPILAN ISTRI NELAYAN KECAMATAN SAMARINDA SEBERANG MELALUI SOSIALISASI DAN WORKSHOP PENGOLAHAN PRODUK HASIL TAMBAK - Anggreini, Putri; Nisaa, Nur Rezky Khairun; Kawareng, Andi Tenri; Wahyuni, Leny Eka Tyas; Prasesti, Gayuk Kalih; Fadilla, Raisa; Badawi, Satriani; Arief, Maryam Jamila; Sinthary, Venna; Siregar, Vita Olivia (Universitas Padjadjaran, 2026)
This community service activity was carried out in Kelurahan Mesjid, Samarinda Seberang, Samarinda City, targeting a group of fishermen’s wives as an effort to empower them through the innovation of functional food and nutraceutical products based on aquaculture products. The program aimed to improve the community’s knowledge and skills in utilizing abundant local aquaculture resources, such as milkfish and shrimp heads as aquaculture waste. The activity began with providing education on the nutritional content, health benefits, and economic potential of shrimp heads and milkfish through interactive socialization sessions. This was followed by a workshop on processing shrimp heads into a nutraceutical product in the form of powdered broth, as well as producing calcium-fortified milkfish nuggets as a functional food. The results showed an increase in participants’ knowledge of nutrition and health, as well as new skills in processing local raw materials into value-added products. This activity is expected to encourage the creation of new business opportunities, improve household income, and support healthy and sustainable food consumption patterns in aquaculture-producing communities. Kegiatan pengabdian masyarakat ini dilaksanakan di Kelurahan Mesjid, Samarinda Seberang Kota Samarinda dengan sasaran kelompok istri nelayan sebagai upaya pemberdayaan melalui inovasi produk pangan fungsional dan nutrasetikal berbasis hasil dan limbah tambak. Program ini bertujuan meningkatkan pengetahuan dan keterampilan masyarakat dalam memanfaatkan sumber daya lokal tambak yang melimpah seperti ikan bandeng dan kepala udang sebagai limbah tambak. Kegiatan diawali dengan memberikan edukasi mengenai kandungan gizi, khasiat, serta potensi ekonomi dari kepala udang dan ikan bandeng melalui sesi sosialisasi interaktif. Selanjutnya dilakukan workshop pengolahan kepala udang menjadi produk nutrasetikal berupa kaldu bubuk, serta pembuatan nugget ikan bandeng terfortifikasi kalsium sebagai pangan fungsional. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan peserta mengenai gizi dan kesehatan, serta keterampilan baru dalam mengolah bahan baku lokal menjadi produk bernilai tambah. Kegiatan ini dapat mendorong terciptanya peluang usaha baru, peningkatan pendapatan keluarga, serta mendukung pola konsumsi pangan sehat dan berkelanjutan di masyarakat area penghasil tambak.